Critical role of mitosis in spontaneous late-onset Alzheimer's disease; from a Shugoshin 1 cohesinopathy mouse model. Issue 19 (18th October 2018) - Rao, Chinthalapally V.; Farooqui, Mudassir; Asch, Adam S.; Yamada, Hiroshi Y.
ABSTRACT: From early-onset Alzheimer's disease (EOAD) studies, the amyloid-beta hypothesis emerged as the foremost theory of the pathological causes of AD. However, how amyloid-beta accumulation is triggered and progresses toward senile plaques in spontaneous late-onset Alzheimer's disease (LOAD) in humans remains unanswered. Various LOAD facilitators have been proposed, and LOAD is currently considered a complex disease with multiple causes. Mice do not normally develop LOAD. Possibly due to the multiple causes, proposed LOAD facilitators have not been able to replicate spontaneous LOAD in mice, representing a disease modeling issue. Recently, we reported spontaneous late-onset development of amyloid-beta accumulation in brains of Shugoshin 1 (Sgo1) haploinsufficient mice, a cohesinopathy-mediated chromosome instability model. The result for the first time expands disease relevance of mitosis studies to a major disease other than cancers. Reverse-engineering of the model would shed light on the process of late-onset amyloid-beta accumulation in the brain and spontaneous LOAD development, and contribute to development of interventions for LOAD. This review will discuss the Sgo1 model, our current "three-hit hypothesis" regarding LOAD development with an emphasis on critical role of prolonged mitosis in amyloid-beta accumulation, and implications for human LOAD intervention and treatment. Abbreviations : Alzheimer's disease (AD); Late-onset Alzheimer's disease (LOAD); Early-onset Alzheimer's disease (EOAD); Shugoshin-1 (Sgo1); Chromosome Instability (CIN); apolipoprotein (Apoe); Central nervous system (CNS); Amyloid precursor protein (APP); N-methyl-d-aspartate (NMDA); Hazard ratio (HR); Cyclin-dependent kinase (CDK); Chronic Atrial Intestinal Dysrhythmia (CAID); beta-secretase 1 (BACE); phosphor-Histone H3 (p-H3); Research and development (R&D); Non-steroidal anti-inflammatory drugs (NSAIDs); Brain blood barrier (BBB)